Medicinal plants for allergic rhinitis: A systematic review and meta-analysis. - Xin Yi Lim; Mei Siu Lau; Nor Azlina Zolkifli; Umi Rubiah Sastu Zakaria; Nur Salsabeela Mohd Rahim; Nai Ming Lai; Terence Yew Chin Tan (PLoS ONE)
Herbal medicine is popularly used among patients who suffer from allergic rhinitis. This systematic review and meta-analysis was conducted to evaluate the efficacy and safety of single medicinal plants in the management of allergic rhinitis. We searched MEDLINE, CENTRAL, and Web of Science for randomised controlled trials which evaluated the use of single medicinal plant for allergic rhinitis among adults and children. Twenty-nine randomised controlled trials (n = 1879) were eligible while 27 (n = 1769) contributed data for meta-analyses. Most studies (studies = 20) compared medicinal plants against placebo and Petasites hybridus was most frequently investigated (studies = 5). Very-low-to-low-certainty evidence suggests that compared to placebo, single medicinal plants may improve overall total nasal symptoms (SMD -0.31, 95% CI -0.59 to -0.02; participants = 249; studies = 5; I2 = 21%) especially nasal congestion and sneezing; and rhinoconjunctivitis quality of life (RQLQ) scores (MD -0.46, 95% CI -0.84 to -0.07; participants = 148; studies = 3; I2 = 0%). Moderate-certainty evidence show no clear differences between single medicinal plants and antihistamine in overall symptoms (Total nasal symptoms: SMD -0.14, 95% CI -0.46 to 0.18; participants = 149; studies = 2; I2 = 0%). As adjunctive therapy, moderate-certainty evidence shows that medicinal plants improved SNOT-22 scores when given as intranasal treatment (MD -7.47, 95% CI -10.75 to -4.18; participants = 124; studies = 2; I2 = 21%). Risk of bias domains were low or not clearly reported in most studies while heterogeneity was substantial in most pooled outcomes. Route of administration and age were identified to be plausible source of heterogeneity for certain outcomes. Medicinal plants appear to be well tolerated up to 8 weeks of use. Clear beneficial evidence of medicinal plants for allergic rhinitis is still lacking. There is a need for improved reporting of herbal trials to allow for critical assessment of the effects of each individual medicinal plant preparation in well-designed future clinical studies.